2013
DOI: 10.1093/ehjci/jet166
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of left ventricular and left atrial mechanics in various entities of aortic stenosis 12 months after TAVI

Abstract: BackgroundTranscatheter aortic valve implantation (TAVI) has been shown to improve prognosis of high-risk patients. Data, however, concerning the impact of TAVI on regional and global left atrial (LA) and left ventricular (LV) mechanics in varying entities of severe aortic stenosis (AS) are sparse, particularly in patients with paradoxical low-flow (PLF) AS or with reduced LV ejection fraction (LVEF). This study evaluated the effects of TAVI on LA and LV mechanics in varying entities of AS 12 months after impl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
42
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(49 citation statements)
references
References 41 publications
(42 reference statements)
5
42
2
Order By: Relevance
“…Recent studies reported an improvement in LA functions after the TAVI procedure in high-risk patients with systolic and diastolic dysfunction [5][6][7]. In the present study, the amelioration of LAA functions soon after the TAVI procedure may have been due to the marked and beneficial effects of the procedure on hemodynamic and echocardiographic parameters.…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…Recent studies reported an improvement in LA functions after the TAVI procedure in high-risk patients with systolic and diastolic dysfunction [5][6][7]. In the present study, the amelioration of LAA functions soon after the TAVI procedure may have been due to the marked and beneficial effects of the procedure on hemodynamic and echocardiographic parameters.…”
Section: Discussionsupporting
confidence: 57%
“…Spethmann et al [7] demonstrated that a global and regional LV and LA mechanics improved 12 months after TAVI. LA function was evaluated with speckle-tracking echocardiography in previous TAVI studies [5][6][7]. To the best of our knowledge, this is the first study to assess LAA functions after TAVI procedure in patients with severe AS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(8) Progressive AS eventually leads to LA failure with decrease in all three strain-derived phasic functions (8), which was also shown here. In other mid-term post-TAVI studies assessing LA remodeling, reservoir (11)(12)(13) and conduit (13) functions improved while contractile function either improved (12) or remained unchanged (13). In our cohort, STE demonstrated some amelioration in both LA compliance and contractility, which might contribute to restoring stroke volume and functional capacity after the TAVI.…”
Section: Left Atrial Myocardial Mechanics In As and Post-tavisupporting
confidence: 57%
“…The fact that changes in LA function were best appreciated by measures of LA deformation (i.e. STE) rather than volumetric methods, also documented by Spethmann et al (13), demonstrates the better sensitivity of STE-based methods. New-onset atrial fibrillation NAF after TAVI is a common complication and is associated with higher rates of cerebrovascular events.…”
Section: Left Atrial Myocardial Mechanics In As and Post-tavimentioning
confidence: 80%